UPAYA MENINGKATAN KETRAMPILAN MEMBACA SERTA MENULIS ANAK MELALUI METODE PERMAINAN KARTU HURUF DAN KARTU KATA DI TK PKK PUTRAGIRI KULON PROGO - Sugiyati Sugiyati (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2019)
The reading and writing ability among children is still low. The children do not know letters and words yet, so that the letter card game in reading and writing activities for children at imitating level is expected to improve student’s reading and writing ability. The subject of this classroom action research was class B students in Putragiri PKK Kindergarten of 2018/2019 academic year. The data collection techniques was observation to measure the scale of reading and writing ability among students. This study conducted in two cycles. Cycle I was held on January 2019, carrying out the national day theme in the form of props story books, worksheets, student magazines, pictures, etc. After cycle I, reflection was done to plan cycle II, which be held on August 2019 with the religious holidays theme and the sub-theme was Qurban and the Idhul Adha day. The results of the study describe that 1) the reading and writing ability among children before being given an action were in the substantial category that means began to develop, 2) the letter card games can improve children's reading and writing skills.